2020
DOI: 10.3390/app10030754
|View full text |Cite
|
Sign up to set email alerts
|

A Circular Economy Virtuous Example—Use of a Stabilized Waste Material Instead of Calcite to Produce Sustainable Composites

Abstract: This work reports and analyzes the mechanical properties of some composites obtained using stabilized waste with epoxy resins E-227. For comparison, correspondent composite samples were realized using calcite as a filler. The recovered stabilized waste was obtained by means of a new method to stabilize municipal solid waste incineration (MSWI) fly ash (FA), based on the use of bottom ash (BA). The aim of this paper is to show that the stabilization process, which can be considered a zero—waste treatment, produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 43 publications
1
14
0
Order By: Relevance
“…The flexural modulus determines how much a sample will bend when a given load is applied, calculated from the slope of the stress vs. The strain deflection curve, as reported by Assi [104]. As reported in Table 1 and as expected, increasing the filler amount in the PP matrix increased the flexural modulus [109].…”
Section: Three Point Bending Testsupporting
confidence: 52%
See 2 more Smart Citations
“…The flexural modulus determines how much a sample will bend when a given load is applied, calculated from the slope of the stress vs. The strain deflection curve, as reported by Assi [104]. As reported in Table 1 and as expected, increasing the filler amount in the PP matrix increased the flexural modulus [109].…”
Section: Three Point Bending Testsupporting
confidence: 52%
“…The most promising results were obtained using these powders as a filler in plastic composites [103]. Several examples have already been proposed, while also discussing the mechanical performances of the obtained composites in comparison to the composites containing natural resources (calcite-CaCO 3 ) [104].…”
Section: Stabilized Fly Ashmentioning
confidence: 99%
See 1 more Smart Citation
“…The obtained stabilized eco-material is a powder that is very similar to the inert material obtained by using similar treatments but using other by-products (such as silica fume) instead of BA for stabilization. This allows for us to suppose that the obtained eco-materials may be used in some applications, already explored for similar products, as a substitute of natural resources [10,33,35,36]. In particular, it was shown that the obtained eco-materials are biologically safe [37][38][39], opening the interesting opportunity of the investigation of their aquatic toxicity in the next future.…”
Section: Appl Sci 2020 10 X For Peer Review 9 Of 12mentioning
confidence: 92%
“…The obtained stabilized eco-material is a powder that is very similar to the inert material obtained by using similar treatments but using other by-products (such as silica fume) instead of BA for stabilization. This allows for us to suppose that the obtained eco-materials may be used in some applications, already explored for similar products, as a substitute of natural resources [10,33,35,36]. The obtained stabilized eco-material is a powder that is very similar to the inert material obtained by using similar treatments but using other by-products (such as silica fume) instead of BA for stabilization.…”
Section: Appl Sci 2020 10 X For Peer Review 9 Of 12mentioning
confidence: 95%